Locals and migrants in the late Ottoman Empire :|a study of state-society and intercommunal relations in the Izmit district, 1877-1914 - Koç, Berk. (Thesis (Ph.D.) - Bogazici University. Atatürk Institute for Modern Turkish History, 2021., 2021)
This thesis investigates the social, economic and political impact of mass migration into the Ottoman Empire after the Russian-Ottoman War of 1877-1914 on locals, migrants and thestate, and their everyday responses to each other in the district of Izmit. By discussing relational changes between the Empire’s largest ethnic-religious millets and the state“on the ground”during watershed moments of the late Ottoman period until the First World War, this study intends to present an analysis of post-migration experiences of ordinarypeople, from locals and migrants to bureaucrats and various other local actors. As a monograph on the Izmit district, the present study seeksat the same time to document changes in admin istration, demography, and socio-economic conditions during the period 1877-1914. The management of settlement, theintegration processes of migrants as well as locals and their responses to the state’s policies and to each other against the backdrop of socio-political and economic tur moilin the Hamidian andSecond Constitutional eras demonstrate that ordinary people were active agents rather than muted objects of state formation.This thesis argues that the daily struggle for survival,andthe competition over land and natural resources transformed nativesa nd migrants in toimportant local actors, but also intensified the antagonism between different ethnic-religious groups, alienating especially the Empire's Christian subjects.
Keywords: İzmit (Turkey) -- History.; Migration, Internal -- Turkey -- Economic aspects.